2022
DOI: 10.1021/acs.analchem.1c05435
|View full text |Cite
|
Sign up to set email alerts
|

Prosit-TMT: Deep Learning Boosts Identification of TMT-Labeled Peptides

Abstract: The prediction of fragment ion intensities and retention time of peptides has gained significant attention over the past few years. However, the progress shown in the accurate prediction of such properties focused primarily on unlabeled peptides. Tandem mass tags (TMT) are chemical peptide labels that are coupled to free amine groups usually after protein digestion to enable the multiplexed analysis of multiple samples in bottom-up mass spectrometry. It is a standard workflow in proteomics ranging from single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The re-scoring was performed as described in Gabriel et al [13]. Briefly, to utilize the RT predictions, the re-scoring pipeline described in Gessulat et al [10] was extended.…”
Section: Re-scoring Workflowmentioning
confidence: 99%
See 3 more Smart Citations
“…The re-scoring was performed as described in Gabriel et al [13]. Briefly, to utilize the RT predictions, the re-scoring pipeline described in Gessulat et al [10] was extended.…”
Section: Re-scoring Workflowmentioning
confidence: 99%
“…Re‐scoring has been shown to hold the potential to substantially increase the confidence and number of peptide identifications [10–12]. While initial research focused on the application on unlabeled peptides, the concept was recently shown to drastically increase the sensitivity and specificity also for data utilizing tandem mass tag (TMT) labeled peptides [13]. This type of multiplexing received a lot of attention over the last years because it parallelizes the analysis of multiple samples and thus increases the scalability of bottom‐up proteomics [14, 15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, ProteomeTools followed the traditional approach to generate a spectral library by synthesizing unique tryptic peptides from the human proteome and acquiring MS/MS data on multiple instrument platforms (Zolg et al, 2017). This was subsequently expanded to include additional tryptic peptides and modified peptides (Zolg et al, 2018), non-tryptic peptides (Wilhelm et al, 2021), and isobarically labeled peptides (Gabriel et al, 2022) to currently consist of more than one million unique synthetic peptides and over 14 million MS/MS spectra. In contrast, MassIVE-KB employed a data-driven approach towards spectral library creation by re-analyzing hundreds of millions to billions of public MS/MS spectra on the MassIVE data repository using sequence database searching (M. .…”
Section: Impact Of Growing and Freely Accessible Spectral Librariesmentioning
confidence: 99%